2013
DOI: 10.1002/smj.2194
|View full text |Cite
|
Sign up to set email alerts
|

When the role fits: How firm status differentials affect corporate takeovers

Abstract: This study explores the implications of interfirm status differentials for firm behaviors in corporate takeover transactions. We argue that the more the status differential between two firms is aligned with expectations of their roles embedded in the specific economic activity, the easier it is for them to agree on the appropriate means to reach consensus on the transaction. Using the empirical context of the U.S. corporate takeover market, we found that the greater the status differential between an acquirer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(38 citation statements)
references
References 103 publications
(157 reference statements)
0
37
0
1
Order By: Relevance
“…Relatedly, Zhao (2009) found that in high-tech industries, acquirers had less pressure to close a deal if they did not depend on acquisitions as external sources of innovation. Finally, status theory suggests that when prospective M&A partners have status differences, the deal motivation and expected behaviors are clearer and the likelihood of deal completion is higher (Shen, Tang, & Chen, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Relatedly, Zhao (2009) found that in high-tech industries, acquirers had less pressure to close a deal if they did not depend on acquisitions as external sources of innovation. Finally, status theory suggests that when prospective M&A partners have status differences, the deal motivation and expected behaviors are clearer and the likelihood of deal completion is higher (Shen, Tang, & Chen, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous studies adopted two methods to measure HR slack: organizational-level human resources minus industry-level average human resources (Mishina et al, 2004), and organizational-level human resources minus predicted-level human resources (Shen, Tang, & Chen, 2014). Because our sample covered all publicly listed firms in each industry, using industry-level information for human resource (the first method) to compute HR slack was more appropriate.…”
Section: Human Resource Slackmentioning
confidence: 99%
“…Shen, Tang, and Chen (2014) propose that, because major decisions such as mergers and acquisitions (M&A), are embedded in a social context, the relative status of acquirer and target firms are likely to influence how investors respond. They find that abnormal returns associated with an acquisition announcement are higher for both the acquirer and target firms when there is a greater differential in acquirer-target status, as measured by the difference in analyst coverage between the two firms.…”
Section: Five Domains Of Analyst Researchmentioning
confidence: 99%